Screening and managing obstructive sleep apnoea in nocturnal heart block patients: an observational study. Issue 1 (December 2016) - Wu, Xu; Liu, Zilong; Chang, Su; Fu, Cuiping; Li, Wenjing; Jiang, Hong; Jiang, Liyan; Li, Shanqun
Abstract Background Nocturnal heart block often occurs in patients with obstructive sleep apnoea (OSA). It is more likely to be undiagnosed in heart block patients who are ignorant of the symptoms of sleep disorder. Berlin Questionnaire (BQ) is a highly reliable way to discover the risk factors of OSA, whereas the validity in sleep-related heart block patients is uncertain. We performed an observational study to address these issues and confirmed the potential protective effect of continuous positive airway pressure (CPAP). Methods Patients who were previously diagnosed with nocturnal heart block with R-R pauses exceeding 2 seconds were retrospective screened from the ECG centre of Zhongshan hospital. These recruited participants completed Berlin Questionnaire and underwent polysomnography synchronously with 24-hour Holter monitoring. A cross-sectional analysis was performed to confirm the association between nocturnal arrhythmia and OSA, as well as to assess the diagnostic accuracy of the BQ. Subsequently, subjects diagnosed with OSA (apnoea-hypopnoea index > 5) underwent 3 consecutive days of CPAP therapy. On the third day, patients repeated 24-hour Holter monitoring within the institution of CPAP. Results The symptoms of disruptive snoring and hypersomnolence in 72 enrolled patients were more related to the occurrence of nocturnal heart block (r = 0.306, 0.226, respectively, p = 0.015, 0.019) than syncope (r = 0.134, p = 0.282) and palpitations (r = 0.106, p = 0.119), which were prominent trait of our study population. The sensitivity, specificity, positive and negative predictive value of the BQ at a cut-off point of 5 of AHI for detecting OSA in heart block patients was 81.0 %, 44.4 %, 91.07 % and 25 %. Nocturnal heart block does not appear to occur exclusively in severe sleep apnoea. The frequent occurrence of arrhythmias in prominent oxygen desaturation supports the correlation between them. CPAP therapy resulted in significant decrease in the average number of episodes of heart block, from 148.58 ± 379.44 to 16.07 ± 58.52 (p < 0.05), same to the change of the longest RR pausing time (from 4.38 ± 2.95 s to 0.57 ± 1.05 s, p = 0.169) in 51 patients. The optimal therapy pressure to make the observed arrhythmia disappeared is 12 cm H2 O. Conclusion Concerning high prevalence of OSA in heart block patients, BQ provided an economical and efficient screening method for OSA. For better management, CPAP therapy is feasible to prevent heart blocks avoiding unnecessary concomitant pacemaker implantation.